UPAYA MITIGASI PENCEMARAN LAUT DENGAN ARTIFICIAL WETLANDS - Sabaruddin Wagiman Tjokrokusumo (Jurnal Teknologi Lingkungan, 2006)
Indonesia is an archipelago country which has coastline up to 81 000 kmwith rich and bountiful wetlands, especially coastal wetlands. Wetlandareas estimated is more than 40.5 millions hectare, including mangroveforest around 6.3 millions hectare. As world environmental condition isdegraded, Indonesia marine and coastal environments have beenexperienced degradation, especially mass fish killed incident quite oftenoccurred in water environments due to eutrophiocation. This incidencehas lead to productive coastal and marine environments to becomehypoxia, means that this is a process of declining oxygen content in thewater column due to organic matter or organic chemicals in waterenvironment were accumulated in coastal and merine environments. Mostscientist precited that this conditions was occurred because of mangroveforest was degraded and already convert to other uses, especially forshrimp pond produvtion and industrial development. World scientist haspraised that mangrove forest is the place to be traditional shrimp pondlocation in years. Scientifically this traditional shrimp pond has praticedand applied ecotechnological approach for increasing stable shrimpproduction in Indonesia. However, this method has been changed latelyfor booming Indonesian shrimp export due to Indonesia economicdevelopment. Therefore, this paper proposed and elaborated theimportant and function of wetlands for not only economic development butalso conserve and mitigate artificial wetlands ecosystem as a wholeecosystem for social, environmental and economic development in thefuture. This paper is also clarify the important of artificial wetlands incoastal and marine landscape.